PENEGAKAN HUKUM TERHADAP PENGEDAR NARKOTIKA DENGAN BERAT NETTO 36 GRAM (STUDI KASUS: PUTUSAN PENGADILAN NEGERI JAKARTA SELATAN NOMOR 637/Pid.sus/2015/PN.JKT.SEL) - Clarissa Meidy Paulus; Dian Andriawan Daeng Tawang (Jurnal Hukum Adigama, 2018)
Due to a rise in cases related to narcotics in Indonesia, the government is stiffening penalties for drug offences. Now, anyone who violates certain drug laws in the nation may end up serving a minimum of four years prison time. Depending on the severity of the violations, the government may even sentence more drug offenders to death. Examines the impact of globalization and new technology on the narcotics industry. Examines the challenges that new technologies, such as the internet, pose to drug law enforcement.  Illicit trafficking of narcotics has been very widespread in Indonesia, Similarly, what happens in this case, someone who ordered narcotics from America-Indonesia. This transaction is done online, But in this case the judge handed down the rehabilitation decision to the narcotics dealer. The order made by the defendant is narcotics with a net weight of 36.1318 grams. From the results of this study based on interviews conducted if giving narcotics to other people with or without the transaction can already be declared as a dealer. Millions of people are affected by drugs in Indonesia. According to the National Agency for Narcotics (BNN), one million people are addicted to drugs with little chance of recovery. Around 1.6 million people occasionally take drugs while 1.4 million are regularly consumers.